The ubiquitin ligase RPM-1 and the p38 MAPK PMK-3 regulate AMPA receptor trafficking. - Eun Chan Park; Doreen R Glodowski; Christopher Rongo (PLoS ONE, 2009)
Ubiquitination occurs at synapses, yet its role remains unclear. Previous studies demonstrated that the RPM-1 ubiquitin ligase organizes presynaptic boutons at neuromuscular junctions in C. elegans motorneurons. Here we find that RPM-1 has a novel postsynaptic role in interneurons, where it regulates the trafficking of the AMPA-type glutamate receptor GLR-1 from synapses into endosomes. Mutations in rpm-1 cause the aberrant accumulation of GLR-1 in neurites. Moreover, rpm-1 mutations enhance the endosomal accumulation of GLR-1 observed in mutants for lin-10, a Mint2 ortholog that promotes GLR-1 recycling from Syntaxin-13 containing endosomes. As in motorneurons, RPM-1 negatively regulates the pmk-3/p38 MAPK pathway in interneurons by repressing the protein levels of the MAPKKK DLK-1. This regulation of PMK-3 signaling is critical for RPM-1 function with respect to GLR-1 trafficking, as pmk-3 mutations suppress both lin-10 and rpm-1 mutations. Positive or negative changes in endocytosis mimic the effects of rpm-1 or pmk-3 mutations, respectively, on GLR-1 trafficking. Specifically, RAB-5(GDP), an inactive mutant of RAB-5 that reduces endocytosis, mimics the effect of pmk-3 mutations when introduced into wild-type animals, and occludes the effect of pmk-3 mutations when introduced into pmk-3 mutants. By contrast, RAB-5(GTP), which increases endocytosis, suppresses the effect of pmk-3 mutations, mimics the effect of rpm-1 mutations, and occludes the effect of rpm-1 mutations. Our findings indicate a novel specialized role for RPM-1 and PMK-3/p38 MAPK in regulating the endosomal trafficking of AMPARs at central synapses.